The Importance of Testing Heart Enzymes - Mohammad.S.Aldosari, Hedaya.B.Sukaik, Emad.A.Alghamdi, Saud.S.Albishi, Marwan.A.Alhodally. Shaker.A.Alshamrani, Abdulahy.E.Turkistani, Makki.A.Digna. Rahma.A.Alrashidi (Journal of International Crisis and Risk Communication Research, 2024)
Approximately 1.7 million people are admitted as the patients of chest pain and the destination is generally the emergency department of a hospital. Only a few of these patients are detected with Acute Coronary Syndrome (ACS), and the remaining are sent back without a diagnosis of cardiac parameters. Such chest pains are may result in sever cardiac arrests and the Cardiac Enzymes must be tested for any such patient. This present study evaluates the scenario with the help of popular and time framed reviews and will present a proper view for the point in question.